Sm10.3, a member of the micro-exon gene 4 (MEG-4) family, induces erythrocyte agglutination in vitro and partially protects vaccinated mice against Schistosoma mansoni infection. - Vicente P Martins; Suellen B Morais; Carina S Pinheiro; Natan R G Assis; Barbara C P Figueiredo; Natasha D Ricci; Juliana Alves-Silva; Marcelo V Caliari; Sergio C Oliveira (PLoS Neglected Tropical Diseases, 2014)
Background The parasitic flatworm Schistosoma mansoni is a blood fluke that causes schistosomiasis. Current schistosomiasis control strategies are mainly based on chemotherapy, but many researchers believe that the best long-term strategy to control disease is a combination of drug treatment and immunization with an anti-schistosome vaccine. Numerous antigens that are expressed at the interface between the parasite and the mammalian host have been assessed. Among the most promising molecules are the proteins present in the tegument and digestive tract of the parasite. Methodology/principal findings In this study, we evaluated the potential of Sm10.3, a member of the micro-exon gene 4 (MEG-4) family, for use as part of a recombinant vaccine. We confirmed by real-time PCR that Sm10.3 was expressed at all stages of the parasite life cycle. The localization of Sm10.3 on the surface and lumen of the esophageal and intestinal tract in adult worms and lung-stage schistosomula was confirmed by confocal microscopy. We also show preliminary evidence that rSm10.3 induces erythrocyte agglutination in vitro. Immunization of mice with rSm10.3 induced a mixed Th1/Th2-type response, as IFN-γ, TNF-α, and low levels of IL-5 were detected in the supernatant of cultured splenocytes. The protective effect conferred by vaccination with rSm10.3 was demonstrated by 25.5-32% reduction in the worm burden, 32.9-43.6% reduction in the number of eggs per gram of hepatic tissue, a 23.8% reduction in the number of granulomas, an 11.8% reduction in the area of the granulomas and a 39.8% reduction in granuloma fibrosis. Conclusions/significance Our data suggest that Sm10.3 is a potential candidate for use in developing a multi-antigen vaccine to control schistosomiasis and provide the first evidence for a possible role for Sm10.3 in the blood feeding process.